2009
DOI: 10.1057/jibs.2009.27
|View full text |Cite|
|
Sign up to set email alerts
|

A “strategy tripod” perspective on export behaviors: Evidence from domestic and foreign firms based in an emerging economy

Abstract: Owing to a production error, a number of values were incorrectly shown in Table 6 of this article. A corrected version of this table is given overleaf.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
314
0
18

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 366 publications
(342 citation statements)
references
References 79 publications
10
314
0
18
Order By: Relevance
“…Therefore being at a disadvantage in comparison to advanced economy markets, internationalising firms from emerging economies are more likely to exploit their cost advantage and pursue a low-cost strategy when entering advanced economy markets (Aulakh, Kotabe, & Teegen, 2000). Cost advantage, measured by production cost ratio, and selling and administrative cost ratio, was found to have a positive effect on export propensity and intensity in a sample of private Chinese manufacturing firms (Gao, Murray, Kotabe & Lu, 2010). Empirical evidence also shows that the positive effects of the cost-based strategy on export performance are stronger among emerging economy firms that internationalise to advanced rather than other emerging economy markets where domestic firms can also draw on low-cost resources and where a differentiation strategy may therefore be more successful (Aulakh et al, 2000).…”
Section: Leverage Of Home-base Resources In Sme Internationalisation mentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore being at a disadvantage in comparison to advanced economy markets, internationalising firms from emerging economies are more likely to exploit their cost advantage and pursue a low-cost strategy when entering advanced economy markets (Aulakh, Kotabe, & Teegen, 2000). Cost advantage, measured by production cost ratio, and selling and administrative cost ratio, was found to have a positive effect on export propensity and intensity in a sample of private Chinese manufacturing firms (Gao, Murray, Kotabe & Lu, 2010). Empirical evidence also shows that the positive effects of the cost-based strategy on export performance are stronger among emerging economy firms that internationalise to advanced rather than other emerging economy markets where domestic firms can also draw on low-cost resources and where a differentiation strategy may therefore be more successful (Aulakh et al, 2000).…”
Section: Leverage Of Home-base Resources In Sme Internationalisation mentioning
confidence: 96%
“…For instance, differentiation competencies, measured by R&D intensity and new product ratio, were found to have a positive effect on export propensity and intensity (Gao et al, 2010), while innovative products and production processes were found to be one of the main sources of positive performance in a case study of Turkish born globals (Kociak & Abimbola, 2009). However, proprietary technology at start-up, like the above mentioned domestic reputation, is found to be more relevant when firms choose to internationalise to other emerging economy markets, as the competitive benefits of such technology are considered to be offering lesser competitive benefits in advanced economies (Yamakawa et al, 2013).…”
Section: Leverage Of Home-base Resources In Sme Internationalisation mentioning
confidence: 99%
“…Gao et al (2010) apply a complex operationalization of Porter's generic strategies, classifying the strategy undertaken between cost leadership and differentiation. Xie et al (2011) measure the market concentration index when comparing the market share of the companies evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…From this formulation, the company's competitiveness is influenced by the environment, that is, external factors would determine the company's strategy (Gao et al, 2010). This model has five strengths: threat of new entrants, bargaining power of suppliers, bargaining power of customers, threat of substitutes, and finally all of these define the competitiveness of the industry (Porter 1979: 141).…”
Section: Industry-based Viewmentioning
confidence: 99%
See 1 more Smart Citation